k = m ∑ n ( k n ) ( m k ) = ( m n ) 2 x
We know that for any positive integers k , n , m such that 0 ≤ m ≤ k ≤ n , the equation above is true.
What is the value of x ?
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
I think some people will be curious how you determined that ∑ k = 0 n − m k ! ( n − m − k ) ! ( n − m ) ! = 2 n − m . Would you mind adding a justification of that to your solution?
The sum of all entries in a row of the pascal's triangle is always 2^x where x is the row number starting from row zero (the first 1)
Let's solve this with a story!
On a planet of n people, m people must be chosen for a council. Each of the non-council members will either be allowed to live or will be killed. In how many ways can this be done?
Approach 1: Choose who lives, then choose the council from the living.
Approach 2: Choose the council, then decide if each of the non-council members lives or is killed.
Both Approach 1 and 2 give all of the possible ways to do this -- and they represent the left-hand and right-hand sides of the equation, respectively. There are 2 choices (lives/killed) for each of n − m people not on the council in Approach 2, so x = n − m .
In Approach 1, we choose k people to live. Now, choose m of those k people to be on the council. Do this for all possible k , noting that we need k ≥ m since the council members must be alive. In approach 2, choose m people to be on the council. Now, for each of the remaining n − m people, decide whether they live or are killed.
I love this :)
Problem Loading...
Note Loading...
Set Loading...
S = k = m ∑ n ( k n ) ( n k ) = k = m ∑ n k ! ( n − k ) ! n ! ⋅ m ! ( k − m ) ! k ! = k = m ∑ n m ! ( n − k ) ! ( k − m ) ! n ! = k = 0 ∑ n − m m ! ( n − m − k ) ! ( k ) ! n ! = m ! ( n − m ) ! n ! k = 0 ∑ n − m k ! ( n − m − k ) ! ( n − m ) ! = ( m n ) k = 0 ∑ n − m ( k n − m ) = ( m n ) 2 n − m Note that ( k n ) = k ! ( n − k ) ! k ! and k = 0 ∑ p ( k p ) = 2 p
⟹ x = n − m